Rapamycin in ischemic stroke: Old drug, new tricks? - Hadley, G; Beard, D; Couch, Y; Neuhaus, A; Adriaanse, B; De Luca, G; Sutherland, B; Buchan, A (SAGE Publications, 2018)
The significant morbidity that accompanies stroke makes it one of the world's most devastating neurological disorders. Currently, proven effective therapies have been limited to thrombolysis and thrombectomy. The window for the administration of these therapies is narrow, hampered by the necessity of rapidly imaging patients. A therapy that could extend this window by protecting neurons may improve outcome. Endogenous neuroprotection has been shown to be, in part, due to changes in mTOR signalling pathways and the instigation of productive autophagy. Inducing this effect pharmacologically could improve clinical outcomes. One such therapy already in use in transplant medicine is the mTOR inhibitor rapamycin. Recent evidence suggests that rapamycin is neuroprotective, not only via neuronal autophagy but also through its broader effects on other cells of the neurovascular unit. This review highlights the potential use of rapamycin as a multimodal therapy, acting on the blood–brain barrier, cerebral blood flow and inflammation, as well as directly on neurons. There is significant potential in applying this old drug in new ways to improve functional outcomes for patients after stroke.